The diversity of nanos expression in echinoderm embryos supports different mechanisms in germ cell specification. Issue 4 (July 2016) - Fresques, Tara; Swartz, Steven Zachary; Juliano, Celina; Morino, Yoshiaki; Kikuchi, Mani; Akasaka, Koji; Wada, Hiroshi; Yajima, Mamiko; Wessel, Gary M.
SUMMARY: Specification of the germ cell lineage is required for sexual reproduction in all animals. However, the timing and mechanisms of germ cell specification is remarkably diverse in animal development. Echinoderms, such as sea urchins and sea stars, are excellent model systems to study the molecular and cellular mechanisms that contribute to germ cell specification. In several echinoderm embryos tested, the germ cell factor Vasa accumulates broadly during early development and is restricted after gastrulation to cells that contribute to the germ cell lineage. In the sea urchin, however, the germ cell factor Vasa is restricted to a specific lineage by the 32‐cell stage. We therefore hypothesized that the germ cell specification program in the sea urchin/Euechinoid lineage has evolved to an earlier developmental time point. To test this hypothesis we determined the expression pattern of a second germ cell factor, Nanos, in four out of five extant echinoderm clades. Here we find that Nanos mRNA does not accumulate until the blastula stage or later during the development of all other echinoderm embryos except those that belong to the Echinoid lineage. Instead, Nanos is expressed in a restricted domain at the 32–128 cell stage in Echinoid embryos. Our results support the model that the germ cell specification program underwent a heterochronic shift in the Echinoid lineage. A comparison of Echinoid and non‐Echinoid germ cell specification mechanisms will contribute to our understanding of how these mechanisms have changed during animal evolution.